The influence of the habits of smokers' family members on the incidence of ARI in toddlers in the working area of the Takeran health center - Putri, Septania Eka Wantika; Ramadanintyas, Karina Nur; Bachrun, Edy (International Journal of Health Literacy and Science, 2024)
ARI is an acute infection of the upper and lower respiratory tracts caused by microscopic or bacterial, viral, or reketsia infections of the body without or accompanied by inflammation of the pulmonary parenchyma. ISPA is also the highest problem in the Takeran sub-district health center. The purpose of this study was to determine the influence of the habits of smokers' family members on the incidence of ispa disease in toddlers in the work area of the Takeran Health Center. This research uses an analytical survey method with a case control approach. The sample of this study was 152 respondents. Data collection was carried out using questionnaire sheets and observation sheets. The data analysis used was univariate, bivariate analysis using Chi Square test. The results showed that the habit of family members smoking did not affect ARI disease in toddlers with a value of pvalue-1000. The conclusion of this study is that there is no influence between the habits of family members smoking with the incidence of ispa in toddlers in the Takeran Health Center Work Area. To overcome the problem of ARI, it is necessary to improve nutritional health, immunization, personal or environmental hygiene and prevent children from coming into contact with people with ARI.